Service of the Fatherland - Bamisaiye Remi (Macmillian Nigeria, 1985)
There were protests and violent demonstrations but still hundreds of new graduates had to obey. The service of the Fatherland scattered young people and their plans for the future to the furthest corners of a great country. In the far south, they met for the first time, Sade, Usman, Biodun, Jibrin, Tim and others, all strangers, all serfs.
Keywords: Juvenile Fiction / Adventure / Service